Who Is in Handicrafts: Tooth Morphology and Age Determination as Tools to Assess Vulnerable Dolphins Sotalia spp. Supplying the Trade of Artisanal Charms in Brazil - Ruenes, Greicy F.; Oliveira, Larissa R. de; Emin-Lima, Renata; Costa, Alexandra Fernandes; Attademo, Fernanda Löffler Niemeyer; Luna, Fábia de Oliveira; Siciliano, Salvatore (Frontiers in Marine Science, 2022)
In Brazil, dolphins’ body parts are commonly used as traditional amulets, named as love-charms, while dolphins’ teeth are commercialized in handcrafted necklaces and bracelets. Recent studies on forensic genetics confirmed the Guiana dolphin, Sotalia guianensis, as the principal target of the love-charms trading, with specimens incidentally captured in gillnets suggested as the primary source. As additional support for these investigations, we characterized tooth morphotypes and ages of dolphins used in the construction of traditional crafts, with the main objective of detecting the dolphin species and population groups most affected by this trade. Teeth collected from necklaces, bracelets, and earrings, sold in public markets from three major cities of Northern and Northeastern Brazil (Belém = 99, São Luís = 4, and Fortaleza =15), were analyzed using four morphological measurements: tooth total length (TL), root diameter (RD), crown length (CL), and cingulum diameter (CID). An unweighted pair group method using arithmetic means (UPGMA), with Euclidean distances as a measure of dissimilarity, multivariate analysis of variance (MANOVA), and principal component analysis (PCA) were used to detect tooth morphotypes in the samples. Ages were obtained by counting the growth layer groups (GLGs) deposited in dentine. Two different groups of teeth were detected presumably belonging to the species Sotalia guianensis and S. fluviatilis. Handicrafts showed a diverse age composition, ranging from 2 to 30 years, with a multimodal distribution (Mean =11 ± 7 SD, Median = 10, Mode = 4, 8, 19), similar to dolphin populations affected by fishery interaction. Results suggested that juveniles individuals and adults younger than 20 years, from both Sotalia species, probably incidentally captured, are the principal source of handicrafts, and raise concern about the greater vulnerability of young age categories presented in this trade.